Small Scale Study on Awareness of Breast Cancer Among Women Aged >35years, the Risk Factors for Breast Cancer and Utilization of Mammogram (International Journal of Nursing Education, 2022)
Introduction: Breast cancer has become an increasing concern and is a major global public health burden. Over100, 000 new breast cancer patients are estimated to be diagnosed annually in India. The health care facilitypattern is diverse, where the benefits of the awareness, early diagnosis and treatment programs is still notavailable in many regions of the country. However, the study aimed to assess the awareness of the small scalecommunity women on breast cancer, its risk factors and utilization of manmmogram as a screening test. Thiswill give an insight for the large scale community study.Methods: The researcher adopted a descriptive research design using a simple random sampling technique tocollect data among 20 unmarried and married women from the village of Badagabettu, Udupi district, Karnataka.Tools were developed and sent for validation. Reliability of tools were done before the data collection. Data wascollected after getting ethical clearance and written consent from the participants. Collected data were analyzedusing the descriptive statistics through SPSS version 16.0.Result: Majority 14 (70%) had moderate knowledge on breast cancer, 6 (30%) had poor knowledge and none (0%)were having good knowledge on breast cancer. The study also revealed that 30% were aware of mammogramand majority 70% were not. The risk factors for breast cancer among women aged 35 years also revealed that15% women had menarche at the age of ≤ 12 years, 5% have the history of having sister diagnosed with breastcancer, 15% did not deliver baby till now and 30% women did not breast feed. There were 5% women who hadthe history of breast biopsy, 10% had the history of taking oral contraceptives within 5 years period and 100%did not have the history of taking alcohol in their life.